2012
DOI: 10.2478/v10125-012-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Life strategies of Viviparidae (Gastropoda: Caenogastropoda: Architaenioglossa) in various aquatic habitats: <i>Viviparus viviparus</i> (Linnaeus, 1758) and <i>V. contectus</i> (Millet, 1813)

Abstract: Viviparidae display two categories of life history traits-one constant and independent of habitat, another depending on ecological conditions. The relatively constant abundance is ensured by clustering in the same places at the same time, sex ratio (prevalence of females), size structure (presence of all size classes, with the largest snails forming the majority), and the high proportion of gravid females in the population. These traits undergo only seasonal variation in particular habitats. Adjustment to envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Some studies (Leung, Grist, Morley, Morritt, & Crane, 2001;Yap & Ed ward, 2010) showed that gastropods which accumu lated relatively higher concentrations of heavy metals have lower growth rates and consequently lower values of allo metric parameters such as shell height and width. In this regard it is worth noting that the growth rates of freshwater gastropods depends on many environmental parameters such as temperature, oxygen availability and their interactions, but also on biotic interactions such as predation and competition (Jakubik, 2012;Jakubik, Koperski, & Lewandowski, 2014). In general we found that population fro m lacustrine environ ment (Skadar Lake) have larger dimensions of all allo metric parameters (Table 5) than specimens from riverine environ ment; the specimens fro m outlet stretches (stream pool) of Matica river are larger than specimens fro m lotic habitat of Zeta river.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (Leung, Grist, Morley, Morritt, & Crane, 2001;Yap & Ed ward, 2010) showed that gastropods which accumu lated relatively higher concentrations of heavy metals have lower growth rates and consequently lower values of allo metric parameters such as shell height and width. In this regard it is worth noting that the growth rates of freshwater gastropods depends on many environmental parameters such as temperature, oxygen availability and their interactions, but also on biotic interactions such as predation and competition (Jakubik, 2012;Jakubik, Koperski, & Lewandowski, 2014). In general we found that population fro m lacustrine environ ment (Skadar Lake) have larger dimensions of all allo metric parameters (Table 5) than specimens from riverine environ ment; the specimens fro m outlet stretches (stream pool) of Matica river are larger than specimens fro m lotic habitat of Zeta river.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the behavioural responses and survival of three species: Viviparus viviparus (L.), Bithynia tentaculata (L.) and Potamopyrgus antipodarum (Gray) to drying of a sandy substratum. These species are ubiquitous in Europe and commonly occur in the near‐shore zone of rivers, streams, reservoirs and lakes (Piechocki, ), where they occupy multiple substratum types, including sand (Piechocki, ; Lodge, ; Jurkiewicz‐Karnkowska, ; Jakubik, ). We hypothesised that these snails would have some adaptations to air exposure, such as burrowing into substratum and horizontal migrations.…”
Section: Introductionmentioning
confidence: 99%
“…The organic matter content may vary depending on the hydrological connectivity of oxbow lakes with the main river channel, for example from 0.23% to 3.97% (from low to medium organic matter content) in oxbow lakes connected with the main river channel or from 0.07% to 31.39% (from low to very high organic matter content) in the lentic oxbow lakes of the Bug River (JaKubIK et al 2006, JaKubIK 2012.…”
Section: Selected Environmental Factors Affecting Oxbow Lake Mollusc mentioning
confidence: 99%